Gypsies in Greater Poland in the 18th century in the light of documents from the State Archives in Poznań - Chodyła, Zbigniew (Balcanica Posnaniensia. Acta et studia, 2001)
The article is devoted to the situation of the Roma population in Greater Poland during the eighteenth century and the ways in which it was perceived by the state administration. The starting point is the problem of the limited number of sources concerning the Roma, resulting from their small population and semi-nomadic way of life. The aim of the study is to analyze unpublished documents preserved in the State Archives in Poznań and to demonstrate their significance for research on the history of the Roma community. The author employs a method of critical analysis of archival sources, namely proclamations and mandates issued by eighteenth-century administrative authorities. The research shows that Roma appeared in official documents mainly in connection with public security, migration, and conflicts with the settled population. Of particular importance are regulations governing the movement of Roma groups and preventing the crossing of state borders. The author also points to the influence of Prussian policy toward the Roma, which encouraged the influx of Roma populations into Greater Poland. The analysis of the sources makes it possible to reconstruct governmental efforts to control the mobility of this group and to better understand its functioning within the realities of the Polish-Lithuanian Commonwealth. The conclusions indicate that the Roma constituted a permanent element of the social structure of eighteenth-century Greater Poland, while relations between them and the administration were shaped primarily by the authorities’ desire to maintain public order and control population movements.